Mobile Phone Chips Reduce Increases in EEG Brain Activity Induced by Mobile Phone-Emitted Electromagnetic Fields - Henz, Diana; Schöllhorn, Wolfgang I.; Poeggeler, Burkhard (Frontiers in Neuroscience, 2018)
Recent neurophysiological studies indicate that exposure to electromagnetic fields (EMF) generated by mobile phone radiation can exert effects on brain activity. One technical solution to reduce effects of EMF in mobile phone use is provided in mobile phone chips that are applied in the mobile phone or on its surface. To date, there are no systematical studies on the effects of mobile phone chip application on brain activity and the underlying neural mechanisms. The present study investigated whether mobile phone chips that are applied in mobile phones reduce effects of EMF emitted by mobile phone radiation on electroencephalographic (EEG) brain activity in a laboratory study. Thirty participants volunteered in the present study. Experimental conditions (mobile phone chip, placebo chip, no chip) were designed in a randomized within-subjects design. Spontaneous EEG was recorded before and after mobile phone exposure for two two-minute sequences at resting conditions. During mobile phone exposure, spontaneous EEG was recorded for thirty minutes during resting conditions, and five minutes during performance of an attention test (d2-R). Results showed increased activity in the theta, alpha, beta and gamma bands during EMF exposure in the placebo and no chip condition. Application of the mobile phone chip reduced significantly effects of EMF on EEG brain activity and attentional performance. Attentional performance level was maintained regarding number of edited characters. Further, a dipole analysis revealed different underlying activation patterns in the chip condition compared to the placebo chip and no chip condition. Finally, a correlational analysis for the EEG frequency bands and electromagnetic high-frequency (HF) emission showed significant correlations in the placebo chip and no chip condition for the theta, alpha, beta, and gamma range. In the chip condition, a significant correlation of HF with the theta and alpha range, but not with beta and gamma range was shown. We hypothesize that reduction of EEG beta and gamma activation is the key neural mechanism in mobile phone chip use that supports the brain to a degree to maintain its natural activity and performance level during mobile phone use.